Hospital autopsy: Endangered or extinct?. Issue 8 (15th June 2015) - Turnbull, Angus; Osborn, Michael; Nicholas, Nick
Abstract : Aim: To determine the hospital autopsy rate for the UK in 2013. Methods: A study of data from a 'Freedom of Information' request to all (n=186) acute NHS Trusts within England (n=160), NHS Boards in Scotland (n=14) and Wales (n=7) and Social Care Trusts in Northern Ireland (n=5). Hospital autopsy rates were calculated from the number of hospital autopsies performed in 2013 as a percentage of total inpatient deaths in the Trust that year. Results: The UK response rate was 99% (n=184), yielding a mean autopsy rate of 0.69%. The mean rates were 0.51% (England), 2.13% (Scotland), 0.65% (Wales) and 0.46% (Northern Ireland). 23% (n=38) of all included respondents had a rate of 0% and 86% (n=143) a rate less than 1%. Conclusions: The decline in hospital autopsy has continued relentlessly and, for better or for worse, the practice is on the verge of extinction in the UK. The study highlights to health professionals and policy makers the magnitude of this decline. Further research should investigate the impact of this on patient safety, clinical audit, public health and medical education.